(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article explores the transformation of the image of the East in post-Soviet fiction through the works of Timur Pulatov and Hamid Ismailov. It analyzes the shifts in perception, representation, and symbolism of the East in the context of the Soviet Union’s collapse and the formation of new cultural identities in Central Asia. Special attention is given to postcolonial approaches and intertextual strategies that reflect the tension between tradition and modernization in the authors’ narratives.